Who was “Big George”? An exploration and critique of Aboriginalist discourse within historical photographic and written texts - Barrington, Robin (Curtin University, 2015)
This thesis is a series of counter-histories to the visual and written textual representations of Jaal, a Yamaji figure who was also known as “Big George the Cannibal” and “King George of Meekatharra”. It is set against the backdrop of violent colonisation and two scientific expeditions to the Murchison in Western Australia during the late 19th and early 20th centuries.